The hypocrites' methods of propaganda: a Quranic perspective - Mohamed Ali Zaroum, Abdulhamid (Faculty of Qur'an and Sunnah Studies(USIM), 2013)

(untitled)
This study is an attempt to shed light on the role of the hypocrites’ leaders in destroying the Islamic community from within as well as the propaganda they use and the psychological warfare they wage against the state. The hypocrites have been blamed for being the “Fifth Column” undermining the security of a nation and endangering the peaceful existence of any multi religious, ethnic and cultural society. As the Qur’an expresses, during the time of the prophet, the hypocrites had made in numerous occasions, several controversial and rebellious statements in a clear sign of unhidden challenge to the prophet’s authority yet in a very deceptive manner. It is extremely important for the Muslims of all generations to be familiar with all sorts of deceptions and propaganda adopted by the hypocrites so as to avoid being trapped and being misled by them. The scope of the study will be the Quranic perspective of the methods, ways and means used by the overbearing hypocrites’ political leaders in deceiving the public. To address the problem under study, three research methods shall be adopted; namely: descriptive, analytical, historical and, to some extent, comparative methods.